Enhanced photocatalytic degradation of dyes under sunlight using biocompatible TiO2 nanoparticles. (9th August 2017) - Bharati, B; Sonkar, A K; Singh, N; Dash, D; Rath, Chandana
Abstract: As TiO2 is one of the most popular photocatalysts, we have studied here the photocatalytic degradation of the most common dyestuffs like rhodamine B (RhB), congo red (CR) and methylene blue (MB), which mainly come from the textile and photographic industries using nanoparticles of TiO2 . Nanoparticles of TiO2 synthesized through a simple and cost effective sol-gel technique crystallizes in the anatase phase, showing a band gap less than that of bulk value. Particles consisting of coherently scattered domains of size 33 nm are found to be agglomerated and polycrystalline in nature. While the degradation rates of MB, CR and RhB after irradiating with a renewable source of energy, i.e. sunlight, show 100% degradation, TiO2 irradiated with UV light of 4.8 eV shows a much slower degradation rate. To use the waste water after photocatalysis, we examine further the biocompatibile nature of the TiO2 nanoparticles by platelet interaction activity, hemolysis effect and MTT assay. It is worth mentioning here that TiO2 nanoparticles are found to be highly hemocompatible, show no platelet aggregation, and the level of intracellular ROS in human platelets does not show significant change in ROS level. We conclude that TiO2 nanoparticles constitute an excellent photocatalyst and biocompatible material, and that after photocatalytic degradation of dye effluents obtained from textile industries, purified water can be used in agriculture and domestic sectors.